Optimizing Renewable Energy System Performance with Real-Time Monitoring Techniques - Deng Jiao; Bouyea Jonathan; Snyder Bradford (Journal of Moeslim Research Technik, 2024)
Research Background: In the face of climate change challenges and the need for sustainable energy, renewable energy systems are becoming increasingly important. However, to maximize the efficiency and performance of renewable energy systems, monitoring techniques are needed that can provide real-time information about the operational conditions of the system. Research Objectives: This research aims to optimize the performance of renewable energy systems through the application of real-time monitoring techniques. This is done by utilizing data obtained directly from sensors connected to the energy system. Research Methods: The research methods used include literature study, system requirements analysis, real-time monitoring infrastructure design, prototype implementation, and functionality testing. The collected data was analyzed to evaluate the system performance and effectiveness of real-time monitoring techniques. Research Results: The implementation of real-time monitoring techniques successfully improves the performance of renewable energy systems by providing accurate and timely information about operational conditions. This allows for more efficient management and responsiveness to changes in environmental conditions or energy demand. Research Conclusion: The application of real-time monitoring techniques can significantly improve the efficiency and performance of renewable energy systems. With real-time information, better decision-making can be made, enabling more effective management and responsiveness to system and environmental dynamics.